2018
DOI: 10.5098/hmt.10.5
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy Ratio and Heat Source Effects on MHD Flow Over an Inclined Non-Linearly Stretching Sheet

Abstract: This paper numerically investigates the magnetohydrodynamic boundary layer convective flow of an electrically conducting fluid in the presence of buoyancy ratio, heat source, variable magnetic field and radiation over an inclined nonlinear stretching sheet under convective surface boundary conditions. The Rosseland approximation is adopted for thermal radiation effects and the non-uniform magnetic field applied in a transverse direction to the flow. The coupled nonlinear momentum, thermal and species concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…To check the correctness of the numerical method employed here, the solutions for some particular cases are put beside those of Ferdows et al, 34 Rashidi et al, 35 and Thumma et al 36 (Tables 1 and 2), and a very good agreement is observed.…”
Section: Validationmentioning
confidence: 88%
See 4 more Smart Citations
“…To check the correctness of the numerical method employed here, the solutions for some particular cases are put beside those of Ferdows et al, 34 Rashidi et al, 35 and Thumma et al 36 (Tables 1 and 2), and a very good agreement is observed.…”
Section: Validationmentioning
confidence: 88%
“…The steady two‐dimensional boundary layer equations for the electrically conducting fluid flow with linear Boussinesq approximations cf 35,36 . are given by ux+vy=0, $\frac{\partial u}{\partial x}+\frac{\partial v}{\partial y}=0,$ uux+vvy=μfρf2uy2+gβTfalse(TTfalse)cos(α)+gβCfalse(CCfalse)cos(α)σB2(x)ρfuνuKptrue′, $u\frac{\partial u}{\partial x}+v\frac{\partial v}{\partial y}=\frac{{\mu }_{f}}{{\rho }_{f}}\frac{{\partial }^{2}u}{\partial {y}^{2}}+g{\beta }_{T}(T-{T}_{\infty })\cos (\alpha )+g{\beta }_{C}(C-{C}_{\infty })\cos (\alpha )-\frac{\sigma {B}^{2}(x)}{{\rho }_{f}}u-\frac{\nu u}{{K}_{p}^{^{\prime} }},$ uTx+vTy=k(ρCp)f2Ty21(ρCp)fqry+Q*(ρCp)ffalse(TTfalse)+μ(ρCp)fuy2, $u\frac{\partial T}{\partial x}+v\frac{\partial T}{\partial y}=\frac{k}{{(\rho...…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 3 more Smart Citations